Importância da correta confecção do prontuário odontológico para identificação humana: relato de caso - Serra, Mônica da Costa [UNESP]; Herrera, Lara Maria [UNESP]; Fernandes, Clemente Maia da Silva (My University, 2012)
The clinical records correspond to a set of documents where all information of the patient is stored. When properly confectioned and filed by the dentist, it may serve as a tool for success in dental expertise. The aim of this paper is to present the importance of proper confection of dental records in human identification by means the presentation of a case of identification, occurred in a São Paulo state city. The notes present in the dental records of the alleged victim were very poor, even with a contradiction. However, having endodontic treatment been performed, the comparative analysis between the radiographs of the skull of the victim (postmortem) and the endodontic treatment of tooth 22 (antemortem) permitted to observe total coincidence between the details of such treatment, and anatomical features present in other dental elements. These important parameters of comparison indicated that the body was of the suspect and, due to the number of coincidences, it could not belong to another individual. Nevertheless, the clinical documentation provided was deficient, and presented contradictory data. Because of its fundamental importance for human identification, it is essential that dental professionals take the necessary care to ensure its proper confection and custody, seeking to make the clinical records also an efficient instrument of consultation in identification cases.

O prontuário odontológico corresponde a um conjunto de documentos onde todas as informações do paciente são guardadas. Quando bem elaborado e arquivado pelo Cirurgião-Dentista, poderá servir de ferramenta para o sucesso em perícias odontolegais. O objetivo desse trabalhoé apresentar a importância da correta confecção do prontuário odontológico na identificação humana por meio de um caso de identificação, ocorrido em uma cidade do interior do estado de São Paulo. As anotações presentes no prontuário odontológico da suposta vítima apresentaram-se bastante deficientes, inclusive com uma contradição. Porém, tendo sido realizado tratamento endodôntico, a análise comparativa entre as radiografias do crânio da vítima (post-mortem) e as do tratamento endodôntico do dente 22 (antemortem) permitiu observar total coincidência entre os detalhes do referido tratamento, além de características anatômicas presentes em outros elementos dentários. Esses parâmetros importantes de comparação indicaram que o corpo encontrado era do suspeito e, devido ao número de coincidências, não seria possível pertencerem a outro indivíduo. Não obstante, a documentação clínica fornecida estava deficiente, e apresentava dados contraditórios. Visto a sua fundamental importância para a identificação humana é mister que os profissionais da Odontologia tomem os cuidados necessários à sua correta elaboração e guarda, buscando fazer do prontuário também um instrumento de consulta eficiente nos casos de identificação.
Importance of the correct confection of the dental records for human identification: case report
Keywords: Forensic anthropology; Forensic dentistry; Clinical record; Radiography; Dental; Odontologia legal; Identificação humana; Perícias odonto-legais; Documentação odontologica; Ciências forenses; Radiologia